A Model for Streamlining Psychotherapy in the RDoC Era: The Example of “Engage” - Alexopoulos, George S. (Mol Psychiatry, 2013)
A critical task for psychotherapy research is to create treatments that can be used by community clinicians. Streamlining of psychotherapies is a necessary first step for this purpose. We suggest that neurobiological knowledge has reached the point of providing biologically meaningful behavioral targets thus guiding the development of effective, simplified psychotherapies. This view is supported by the Research Domain Criteria (RDoC) Project, which reflects the field’s consensus and recognizes the readiness of neurobiology to guide research in treatment development.